Influence of the estrous cycle on the sensitivity to catecholamines in right atria from rats submitted to foot-shock stress - Vanderlei, L. C M [UNESP]; Marcondes, F. K.; Lanza, L. L B; Spadari-Bratfisch, R. C. (My University, 1996)
We investigated the mechanisms of the alterations in sensitivity to catecholamines in right atria from female rats exhibiting regular 4-day estrous cycles after three foot-shock sessions at estrus, metestrus, and diestrus or at diestrus, proestrus, and estrus. Right atria from stressed rats sacrificed at diestrus showed subsensitivity to noradrenaline and adrenaline. After in vitro sympathetic denervation (38 μM 6-hydroxydopamine) plus inhibition of neuronal reuptake (0.1 μM desipramine) subsensitivity to noradrenaline was abolished, but it was again evident when extraneuronal uptake was also inhibited (10 μM phenoxybenzamine and 30 μM corticosterone). The same pretreatment abolished the subsensitivity to adrenaline. After addition of 1 μM butoxamine, a β2-adrenoceptor antagonist, the tissues from stressed rats were subsensitive to adrenaline. Right atria from stressed rats sacrificed at estrus did not show any alteration in sensitivity to catecholamines. We conclude that after foot-shock stress, right atria from female rats sacrificed at diestrus showed subsensitivity of the chronotropic response to catecholamines as a result of a conformational alteration of β1-adrenoceptors, simultaneously with an increase in β2-adrenoceptor-mediated response. The mechanisms seem to be similar to those which underlie stress-induced alterations in catecholamine sensitivity in right atria from male rats. However, during estrus there are some protective factors that prevent the effects of stress on right atria.
Keywords: Adrenaline; Diestrus; Estrus; Female rats; Foot-shock stress; Noradrenaline; Subsensitivity; adrenalin; butoxamine; catecholamine derivative; corticosterone; desipramine; noradrenalin; oxidopamine; phenoxybenzamine; animal experiment; animal tissue; chronotropism; controlled study; denervation; diestrus; drug sensitivity; estrus cycle; female; heart right atrium; in vitro study; nonhuman; priority journal; rat; stress; Adrenergic beta-Antagonists; Animals; Atrial Function; Butoxamine; Electroshock; Epinephrine; Female; Heart Atria; Heart Rate; Norepinephrine; Rats; Rats, Wistar; Stress